MEMES DE INTERNET: uma proposta didática para leitura e produção de textos nas aulas de Língua Portuguesa no Instituto Federal do Maranhão/Campus São Luís - Monte Castelo - TERRADO, Luisyane de Maria Carlos (2024)
The research entitled “INTERNET MEMES IN THE CLASSROOM: a didactic proposal for teaching Portuguese Language” is part of the Postgraduate Program in Basic Education Teaching Management – PPGEEB, Professional Master’s Degree, Teaching and Learning research line in Basic Education, from the Federal University of Maranhão – UFMA. The general objective is to investigate how the internet meme genre can contribute to the production of texts by students in the 1st year of Integrated High School, at IFMA/Campus São Luís-Monte Castelo, aiming to create an E-book with didactic guidelines that direct the teacher's work with the meme genre. And, as specific: identify which conception(s) of language underlie(s) the teaching work for teaching Portuguese Language; identify which knowledge is mobilized by students to produce memes in Portuguese language classes; develop strategies for reflective reading of memes that contribute to the production of critical texts in Portuguese language classes; produce an e-book containing teaching guidelines with the aim of encouraging work with internet memes in the classroom, from a perspective of Multiliteracies and dialogic Pedagogy. The research is based on the theoretical assumptions of the New London Group (1996), Cope and Kalantzis (2000; 2015), Rojo (2013; 2009); Rojo and Barbosa (2015); for conceptions of multiliteracies; in Bakhtin (2016, 2014, 2003) for conceptions of gender; and in Marcuschi (2005) for conceptions of emerging digital genres; in official education documents, such as the BNCC (2018), which highlights the relevance of teaching/learning being developed through genres, including digital ones and, among them, memes; and, in Arce (2019), Testa (2020) and Silva (2020) who developed research on the internet meme genre. The research is of an applied nature, based on the assumptions of pedagogical intervention. The research subjects were a Portuguese language teacher and 1st year students, Visual Communication Course at IFMA. The data generation process was supported by the following instruments: observation; questionnaire and semi-structured interview. In general, the results obtained show that Internet Memes differ from other genres due to their dynamism and rapid propagation, this allowed us to present the product “E-book – Dialogando com Memes de Internet: digital experiences for the classroom” fruit of actions and reflections with a view to contributing to the teaching and learning process. The conclusions revealed that, when the teaching of the Portuguese language is carried out through genres that are “close” to the students, teaching and learning become pleasurable, and the process of constructing texts is given new meaning from memic perspectives.